Digital Era Human Resources Development Management at Markaz Tahfidz Balita Al-Firdaus: Manajemen Pengembangan Sumber Daya Manusia Era Digital di Markaz Tahfidz Balita Al Firdaus - Amaliah, Lillah; Wahyuni, Akhtim (Indonesian Journal of Innovation Studies, 2026)
General Background: Human resource development is essential for educational institutions operating in the digital era. Specific Background: Markaz Tahfidz Balita Al-Firdaus requires competent educators to support Quran memorization learning for young children through digital learning facilities. Knowledge Gap: The management of human resource development in this specific tahfidz setting requires systematic analysis. Aims: This study analyzes digital-era human resource development management at Markaz Tahfidz Balita Al-Firdaus. Results: Using descriptive qualitative methods, observations, interviews, and documentation identified four stages: Plan, involving training needs analysis, training materials, and program evaluation; Do, covering knowledge, abilities, and skills; Check, involving daily, weekly, and six-month performance evaluation; and Action, involving motivation, guidance, training, and upgrading learning facilities. Novelty: The study applies the PDCA framework to human resource development in a toddler tahfidz institution. Implications: The findings indicate that systematic and continuous management supports educator development and learning management. Key Findings Highlights Training needs are identified through skills, performance, and Quran memorization assessments. Educator development covers knowledge, classroom abilities, and teaching skills. Continuous evaluation leads to motivation, guidance, training, and facility upgrading. Keywords: Human Resource Development, Digital Era, Tahfidz Education, PDCA, Educator Development